Fatima Jinnah : Mother of the Nation - Pirbhai, M. Reza (South Asia Cambridge University Press, 2018)
The first major scholarly biography of the influential female activist Fatima Jinnah. This is essential reading for those interested in modern South Asian and Islamic history, particularly the themes of gender, colonialism, the roots of Muslim nationalism and the early challenges facing the Pakistani state.
Include Bibliography and Index
Keywords: Politicians -- Women politicians -- Jinnah, Fatima, 1894-1967